2017
DOI: 10.1038/s41467-017-01215-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot measurement of the orbital-angular-momentum spectrum of light

Abstract: The existing methods for measuring the orbital-angular-momentum (OAM) spectrum suffer from issues such as poor efficiency, strict interferometric stability requirements, and too much loss. Furthermore, most techniques inevitably discard part of the field and measure only a post-selected portion of the true spectrum. Here, we propose and demonstrate an interferometric technique for measuring the true OAM spectrum of optical fields in a single-shot manner. Our technique directly encodes the OAM-spectrum informat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 53 publications
0
59
0
Order By: Relevance
“…However, such experiments rely on the fragile stability of interferometers and coincidence techniques over time. A novel version of this technique demonstrates the measurement of the CF through single-shot acquisition of interferograms [23,24], therefore eliminating stability problems. Similarly, this issue does not play a role if the interference is observed between two different azimuthal parts of the same beam, like in a double-slit experiment [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, such experiments rely on the fragile stability of interferometers and coincidence techniques over time. A novel version of this technique demonstrates the measurement of the CF through single-shot acquisition of interferograms [23,24], therefore eliminating stability problems. Similarly, this issue does not play a role if the interference is observed between two different azimuthal parts of the same beam, like in a double-slit experiment [25].…”
Section: Introductionmentioning
confidence: 99%
“…OAM beams have envisioned applications in optical communication technology 19 , 20 , quantum information processing 21 , and optical manipulation 22 . Since these applications require a precise knowledge of the OAM mode content, the detection and analysis of paraxial OAM beams have been a subject of great interest 23 26 . However, a quantitative assessment of the purity with which plasmonic nanostructures, such as spiral nanostructures, transfer OAM to scattered, spherical waves is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Through experiments it has been suggested that specific effects attributable to the OAM of light can be identified. Schemes to filter OAM states have been proposed and proposals for beam splitters for the OAM states aimed at achieving quantum information processing have also been developed . There have also been several discussions on the cloning of OAM states and network‐based OAM .…”
Section: Introductionmentioning
confidence: 99%